2019
DOI: 10.1371/journal.pone.0211436
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of gliadin, a component of wheat gluten, in increased intestinal permeability leading to non-steroidal anti-inflammatory drug-induced small-intestinal damage

Abstract: Gliadin, a component of wheat gluten known to be an important factor in the etiology of celiac disease, is related to several other diseases through its enhancing effect on intestinal paracellular permeability. We investigated the significance of gliadin in non-steroidal anti-inflammatory drug (NSAID)-induced small-intestinal damage in mice. 7-week-old C57BL/6 male mice were divided into the following groups: standard diet group, in which mice were fed with wheat-containing standard rodent diet (CE-2); gluten-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…Bile acids are especially instrumental factors that highly aggravate NSAID-induced damage as there are reports showing that NSAID alone can trigger less macroscopic injuries in spite of increasing membrane permeability and inflammation in bile duct-ligated rats [142]. An interesting study revealed that insoluble dietary fibers and gliadin (contained in wheat gluten) lead to intestinal epithelial injury and increase in intestinal permeability mainly when mucus levels are low due to NSAID usage [143][144]. It was evident from the post hoc analysis of the data, obtained from Multinational Etoricoxib and Diclofenac Arthritis Long-term (MEDAL) trial that small intestinal complications accounted for 40% of severe gastrointestinal complications in patients using NSAIDs [145].…”
Section: Risk To the Gastric Mucosal And Small Bowel Injuriesmentioning
confidence: 99%
“…Bile acids are especially instrumental factors that highly aggravate NSAID-induced damage as there are reports showing that NSAID alone can trigger less macroscopic injuries in spite of increasing membrane permeability and inflammation in bile duct-ligated rats [142]. An interesting study revealed that insoluble dietary fibers and gliadin (contained in wheat gluten) lead to intestinal epithelial injury and increase in intestinal permeability mainly when mucus levels are low due to NSAID usage [143][144]. It was evident from the post hoc analysis of the data, obtained from Multinational Etoricoxib and Diclofenac Arthritis Long-term (MEDAL) trial that small intestinal complications accounted for 40% of severe gastrointestinal complications in patients using NSAIDs [145].…”
Section: Risk To the Gastric Mucosal And Small Bowel Injuriesmentioning
confidence: 99%
“…As a result of such initial disorders brought by COX inhibition and the topical effects on mitochondria, intestinal permeability is increased with the disruption of the barrier function, which facilitates the invasion of the small bowel by luminal injury factors such as enterobacteria and bile. Furthermore, recent studies have suggested that dietary factors are involved in increased intestinal permeability during the development of NSAIDs-induced damage: Insoluble dietary fibers contribute to the surface damage of the intestinal epithelium when the mucus is decreased by NSAIDs' administration [66], and gliadin, a component of wheat gluten, increases the intestinal permeability via the epidermal growth factor receptor-dependent signaling pathway [67]. All these events lead to promoting a series of inflammatory events sufficient for inducing macroscopic ulceration.…”
Section: Pathophysiology Of Nsaids-induced Enteropathy Cox Inhibitionmentioning
confidence: 99%
“…and T.K.). For evaluation, a modified histological scoring system was used [ 25 ]. The histological score ranged from 0 to 13 and was divided into the following six categories: epithelium (0 = normal, 1 = flattened, 2 = loss of epithelial continuity, 3 = severe denudation), villus shape (0 = normal, 1 = short and rounded, 2 = extremely short and thick), villus tip (0 = normal, 1 = damaged, 2 = severely damaged), stroma (0 = normal, 1 = slightly retracted, 2 = severely retracted), inflammation (0 = no infiltration, 1 = mild infiltration, 2 = severe infiltration), and crypt status (0 = normal, 1 = mild crypt loss, 2 = severe crypt loss).…”
Section: Methodsmentioning
confidence: 99%